EFFECT OF SOIL SALINITY ON WATER EXCHANGE PARAMETERS OF FINE-FIBER COTTON VARIETIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article discusses the effects of soil salinity on some water exchange parameters of fine-fiber cotton varieties Surkhon-111 and Termiz-3 based on experiments. The transpiration rate and water retention rate of leaves of cotton varieties significantly depend on the development phases of the varieties, and it was noted that the transpiration rate is highest at the boll stage and the water retention rate of leaves is highest at the budding stage.